BAGAIMANAKAH PERAN SERIKAT PEKERJA DALAM PENENTUAN UPAH SETELAH BERLAKUNYA PERATURAN PEMERINTAH NO. 78 TAHUN 2015 TENTANG PENGUPAHAN - Wawan .; Andari Yurikosari (Fakultas Hukum Universitas Tarumanagara, 2018)
Law no. 13 of 2003 on Manpower clearly regulates the determination of district minimum wage set by the Governor by taking into account the recommendations of the Wage Council, the Wage Council conducts a market survey to establish the standard of living needs of a person. The Manpower Act states that in the process of establishing a minimum wage the need for negotiations between the wage council, trade unions and employers' organizations. While the Governor looks for the middle line to set the minimum wage. After the issuance of Government Regulation no. 78 Year 2015 on Wages, minimum wage determination is no longer through negotiation, but through minimum wage calculation formula that is with the minimum wage of the current year, inflation and gross domestic income. The author intends to find out about the role of unions after the issuance of Government Regulation no. 78 of 2015 on remuneration, and determination of minimum wage. The author examines this issue using nomative research methods supported by expert interview data. The author analyzes that after the issuance of the Government Regulation on Remuneration of unions has ceased to function in the protection of workers' welfare.